Transbronchial biopsy without fluoroscopy: a five year experience in outpatients. Issue 11 (November 1989) - de Fenoyl, O; Capron, F; Lebeau, B; Rochemaure, J
Abstract : Transbronchial biopsy is the technique of choice for obtaining tissue for histological diagnosis in many pulmonary disorders. The procedure has usually been carried out as an inpatient procedure with the use of fluoroscopy, though this policy has recently been questioned. This report concerns a five year experience of 174 transbronchial biopsies performed without fluoroscopy as an outpatient procedure in patients with interstitial lung disease or a suspicion of sarcoidosis. Chest radiography was carried out only if the patient developed symptoms. No major complications were encountered and the overall complication rate was low. Pneumothorax occurred in six patients (3.4%), only one of whom required intercostal intubation, and bleeding of more than 30 ml occurred in two patients. Histological diagnosis was obtained in 154 patients (88%). In the experience of this group transbronchial biopsy has been safe when carried out as an outpatient procedure without fluoroscopic guidance.